11 The bladder and the brain: exploring functional urological symptoms. (28th May 2019) - Hoeritzauer, Ingrid
Abstract : Ingrid Hoeritzauer is a neurologist who also has a degree in psychology. She works with the Functional Research Team led by Jon Stone and Alan Carson in Edinburgh and received an ABN/Patrick Berthoud Clinical Research Training Fellowship. Her research interests are observational studies in functional neurological disorders and cauda equina syndrome and her current research focuses on the interface between Uro-Neurology and functional neurological disorders. This talk will review the current understanding of the bladder-brain axis, and the evidence linking functional disorders, including Functional Neurological Disorder (FND), to bladder symptoms including urinary retention and in the study of patients who present with cauda equina syndrome but have normal scans. Uro-Neurology is the connection between urological symptoms and the neurological system, comprising a complex bladder-brain network involving the brain, spinal cord, sacral nerves and peripheral (pelvic) nerves. Since the time of Charcot there have been hypotheses that urological symptoms, particularly idiopathic urinary retention and overactive bladder symptoms, were part of a functional disorder. However, in the 1980s urethral EMG changes in women with idiopathic urinary retention led to a view that so called 'psychogenic' urinary retention was a primary disorder of the urethral sphincter. Changing views of FND in the last 10 years mean that urological symptoms are once again being investigated as a potential part of functional disorders. Patients presenting with chronic idiopathic urinary retention, diagnosed as Fowler's syndrome, or presenting with acute urinary retention and possible cauda equina syndrome, have been found to have high levels of functional disorder and FND comorbidity 1 2 . Additionally, recent papers have suggested central sensitisation as the mechanism of action in patients with idiopathic overactive bladder symptoms. 3 This newly re-energised field of study requires further exploration, such as investigation of the effect of pathomechanical and medication induced urological symptoms on patients with functional disorders. A practical guide to how to discuss likely functional urological symptoms based on the current level of knowledge will conclude the talk. References: Hoeritzauer I, Stone J, Fowler C, Elneil-Coker S, Carson A, Panicker J. Fowler's syndrome of urinary retention: A retrospective study of co-morbidity. Neurourol Urodyn2016;35:601–3. Hoeritzauer I, Pronin S, Carson A, Statham P, Demetriades AK, Stone J. The clinical features and outcome of scan-negative and scan-positive cases in suspected cauda equina syndrome: a retrospective study of 276 patients. J Neurol2018;265:2916–26. Leue C, Kruimel J, Vrijens D, Masclee A, Van Os J, Van Koeveringe G. Functional urological disorders: A sensitized defence response in the bladder-gut-brain axis. Nat. Rev. Urol. 2017;14:153–63.